The Effect Of Taxpayer Awareness, Public Service Accountability, And Tax Sanctions On Motor Vehicle Taxpayer Compliance - Tiara Kuilim; Harun Blongkod; Mahdalena Mahdalena (PT. Publikasiku Academic Solution, 2023)
This study aims to determine the effect of taxpayer awareness, public service accountability and tax sanctions on motor vehicle taxpayer compliance. The data used is primary data obtained by distributing questionnaires to motor vehicle taxpayers in SAMSAT Gorontalo City. The determination of samples in this study used the slovin formula so that the number of samples in this study amounted to 139. Data analysis in this study used SEM (Structural Equation Modeling) analysis with the help of the AMOS program. The results showed that 1) Taxpayer awareness has a significant effect on motor vehicle taxpayer compliance, 2) Public service accountability has an insignificant effect on motor vehicle taxpayer compliance, 3) Tax Sanctions have no significant effect on motor vehicle taxpayer compliance, 4) Taxpayer awareness, public service accountability, and tax sanctions simultaneously affect motor vehicle taxpayer compliance